Empowerment Of Communities Through Preservation Of Traditional Tourism Villages To Increase Local Economy In Trenggalek District, East Java Province - Muchammad Firman Mauludin; Sudarmiatin Sudarmiatin (Institute of Computer Science (IOCS), 2021)
Abundant natural wealth and cultural peculiarities are one of the assets in the development of the community's economy. Likewise in Trenggalek Regency. Not only beautiful natural conditions, Trenggalek Regency has traditional arts and cultural offerings that are rich in meaning and exoticism. The potential of Trenggalek Regency can basically contribute to improving the local economy so as to reduce poverty levels. Therefore the aim of this research is to implement community empowerment in the preservation of traditional tourism villages in order to improve the local economy in Trenggalek Regency. This research uses an action research approach with a community empowerment strategy based on the ABCD (Aset Based Community Development) methodology or Asset-Based Community Assistance. The collected research data is then processed and analyzed descriptively. The results showed that community empowerment activities in the preservation of traditional tourism villages began with an FGD to map and identify assets and customs in the location of traditional tourism villages, which was then carried out in accordance with community expectations. WatulimoSubdistrict has customs/ culture according to their respective local wisdom. The impacts that arise from the implementation of community empowerment and the plan for the preservation of traditional tourism villages are varied. The implementation of empowerment is able to have a positive impact on the preservation and development of traditional tourism villages, such as the formation of customary institutions and the construction of cultural houses.